Creative strategies : idea management for marketing, advertising, media and design - Pricken, Mario (Thames & Hudson, 2010)
Suitable for designers and advertising creatives, this book showcases 230 ad campaigns. It demonstrates how brilliant ideas can be used to forge more fruitful relationships between creatives and clients. It asks provocative questions, challenges stale routines, and suggests exercises that will stimulate discussion and kick-start the imagination.